Trade, technology, and prosperity: An account of evidence from a labor-market perspective - Marc-Andreas Muendler (World Trade Organization (WTO), 2017)
Trade and technological change continually alter the workplace and labor-market outcomes, with consequences for economy-wide welfare and the distribution of real incomes. This report assesses the state of economic research into those areas, with a particular focus on empirical methodologies and their adequacy for an assessment of general-equilibrium outcomes. While difference-in-differences techniques and instrumental- variable approaches provide answers, they exhibit shortcomings that limit conclusiveness. Recent advances in structural estimation of multi-country and multisector models that allow for reallocation frictions in domestic labor markets hold promise to deliver more definite empirical answers. Interestingly, a conclusion from a two-decades old strand of literature seems to be vindicated by conclusions from a related recent literature: roughly one-quarter of changes in labor-market outcomes (wage inequality then and manufacturing job losses now) was predicted by trade integration and roughly one-third by technological change. The remainder of changes in labor-market outcomes remains unaccounted. The report offers candidate explanations, rooted in recent evidence, how interactions between globalization, technological progress, and structural change may account for that remainder.
Keywords: F16; F32; J23; J24; L16; O14; 330; trade; current account balance; automation; choice of technology; industrial structure and structural change; labor-market outcomes; employment; jobs; wages; inequality